Interdisciplinary Actions in the Physical and Educational Care of Older Adults in the Community - Pereira, Francisco Barbosa; Martínez, Carlos Manuel Fuentes; Suzarte, Julio César Pérez; Pereira, João Dias; Santana, Giraldo Machuat (Jurnal Sosial Teknologi, 2025)
The complexity of aging processes requires integrated care that transcends disciplinary boundaries. This study addresses the research problem: "How can interdisciplinary actions improve physical and educational care for older adults in the community of Becora, Díli, Timor-Leste?" The research identified critical gaps between medical care and complementary disciplines such as physical education and nutrition, demonstrating a pressing need for coordinated interdisciplinary interventions. This study employed theoretical methods (historical-logical analysis, documentary analysis, systematization, and modeling), empirical methods (surveys, interviews, and expert consultations), and statistical methods (descriptive and inferential analysis) to develop and assess a comprehensive interdisciplinary care model. The primary finding reveals that interdisciplinary coordination across medical, nutritional, physical, and educational domains is essential for effective community-based geriatric care. The research identifies four key interdisciplinary nodes—physical, social, emotional-cognitive, and comprehensive functional dimensions—that integrate specialized expertise to promote healthy aging. Results demonstrate significant improvements in participants' overall quality of life, autonomy, and well-being. The main contribution of this research is the systematic identification and validation of interdisciplinary actions as a feasible and effective strategy for improving physical and educational care for older adults in community settings. This evidence-based approach provides a replicable model for other resource-limited communities addressing aging populations.